Silica‐supported morpholine alkaline ionic liquid catalysts for preparation of biodiesel. (1st December 2020) - Zeng, Xiang‐Rui; Wang, Lu‐Lu; Wang, Ji‐Lin
Abstract: Biodiesel was synthesized by transesterification of soybean oil and methanol over a silica‐supported morpholine alkaline ionic liquid catalyst (SILC). Characterization of SILC was performed using 1 H‐nuclear magnetic resonance ( 1 H‐NMR), Fourier‐transform infrared spectroscopy (FT‐IR), x‐ray diffraction, thermogravimetric analysis (XRD), and nitrogen adsorption‐desorption isotherms. Transesterification proceeded satisfactorily over SILC at ambient pressure and without simultaneous water removal. Under optimal reaction conditions, including 60°C, 4 hours, reactant/catalyst molar ratio of 14/1, and 3‐wt% catalyst, a high yield of biodiesel (94.5%) was obtained. SILC's reusability was more than six times, with no obvious decrease in catalytic activity observed. Abstract : Supported catalyst SILC efficiently catalyzes vegetable oil to produce biodiesel.